Minor Salivary Gland Surgery and Histopathological Scoring System: A Systematic Review. (11th October 2022) - Pellegrini, Matteo; Pulicari, Federica; Kuhn, Elisabetta; Scribante, Andrea; Spadari, Francesco
Abstract : Sjögren's syndrome is a systemic autoimmune disease characterized by chronic inflammation of the exocrine glands with an associated functional deficit. The clinical picture is characterized by symptoms such as dry eyes (xerophthalmia) and dry mouth (xerostomia). The disease is defined as primary if no other autoimmune diseases are associated, otherwise, it is defined as secondary. A systematic review was made using the databases PubMed (MEDLINE), Scopus, and keywords "biopsy, " "classification, " "clinical pathology, " "salivary glands, " and "Sjogren's syndrome." The diagnosis of Sjögren's syndrome is based on a combination of clinical, serologic, instrumental, and histological features. In addition to ocular tests, a biopsy of the minor salivary glands represents one of the most relevant examinations for the diagnosis. In fact, the evaluation of specific histopathological features represents one of the most important criteria proposed in the last international consensus of 2016, which developed the most recent classification criteria for Sjögren's syndrome. Knowledge of classification criteria, minor salivary gland biopsy techniques, and histopathological features are essential for the clinician to evaluate the pathology report and make a diagnosis of Sjögren's syndrome. The aim of this review is to describe the classification criteria of the disease proposed to date, the main biopsy techniques used to analyze the minor salivary glands, and finally, the histopathological diagnostic scoring systems currently applied.